2021
DOI: 10.1007/s11255-020-02757-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing dialysis dose in the context of frailty: an exploratory study

Abstract: Introduction Frailty is a multicausal syndrome characterized by a decrease in strength, resistance and physiological function, which makes the individual vulnerable and dependent, and increases his/her mortality. This syndrome is more prevalent among older individuals, and chronic kidney disease patients, particularly those on dialysis. Dialysis dose is currently standardized for hemodialysis (HD) patients regardless of their age and functional status. However, it has been postulated that the dialysis dose req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Keeping improving the quality of hemodialysis treatment could potentially improve these dialysis-related variables and might become the potential measure in reducing the prevalence of frailty among dialysis patients. 19 , 25 These confirmed hemodialysis-related risk factors also remind us that we should make more accurate interventions in frailty prevention among hemodialysis patients.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Keeping improving the quality of hemodialysis treatment could potentially improve these dialysis-related variables and might become the potential measure in reducing the prevalence of frailty among dialysis patients. 19 , 25 These confirmed hemodialysis-related risk factors also remind us that we should make more accurate interventions in frailty prevention among hemodialysis patients.…”
Section: Discussionmentioning
confidence: 67%
“…The prevalence of frailty has been reported much higher in the dialysis population. 19 , 20 Johansen et al 9 reported that the prevalence of frailty in the incident hemodialysis and peritoneal dialysis patients was 67.7% in the Dialysis Morbidity and Mortality Study (DMMS) Wave 2. Other reports from Japan and Korea showed that the prevalence of frailty was 21.4% and 34.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%